Meta-Analysis of Hepatic Arterial Infusion for Liver Metastases From Colorectal Cancer - Zhang, Yan; Wang, Kaili; Yang, Tao; Cao, Yibo; Liang, Wanling; Yang, Xiangdong; Xiao, Tianbao (Frontiers in Oncology, 2021)
The aim of the present study was to evaluate the potential benefits of hepatic arterial infusion chemotherapy (HAIC) in the management of colorectal liver metastases (CRLM). Electronic databases, including PubMed, EMBASE, Medline, Web of Science and Cochrane Library, were comprehensively searched from inception to November 2020. Prospective randomized trials with HAIC vs. systemic chemotherapy (SC) were selected. The overall survival (OS), tumor response rates (RRs), progression-free survival (PFS) and corresponding 95% confidence intervals (CIs) were assessed in the meta-analysis. Subsequently, the heterogeneity between studies, sensitivity, publication bias and meta-regression analyses were performed. Finally, 18 studies, which contained 1,766 participants (922 in the HAIC group and 844 in the SC group) were included. There was a significantly higher OS rate in the HAIC as palliative treatment group (HR, 0.17; 95% CI, 0.08-0.26; P=0.000) and HAIC as adjuvant treatment group compared with SC group (HR, 0.63; 95% CI, 0.38-0.87; P=0.000). The complete and partial tumor RRs were also increased significantly in the HAIC as palliative treatment group (RR=2.09; 95% CI, 1.36-3.22; P=0.001) and as adjuvant treatment group compared with SC group (RR, 2.14; 95% CI,1.40-3.26; P=0.000). However, PFS did not differ significantly between the HAIC and SC groups (P＞0.05). Meta-regression analysis showed potential covariates did not influence on the association between HAIC and OS outcomes (P＞0.05). The results of the present study suggested that HAIC may be a potential therapeutic regimen that may improve the outcomes of patients with CRLM. The present meta-analysis has been registered in PROSPERO (no. CRD 42019145719).